2008
DOI: 10.5194/angeo-26-2911-2008
|View full text |Cite
|
Sign up to set email alerts
|

Solar and geomagnetic activity effects on mid-latitude F-region electric fields

Abstract: Abstract. Diurnal patterns of average F-region ionospheric drift (electric field) and their dependence on solar and geomagnetic activity have been defined using digital ionosonde Doppler measurements recorded at a southern mid-latitude station (Bundoora 145.1 • E, 37.7 • S geographic, 49 • S magnetic). A unique database consisting of 300 907 drift velocities was compiled, mostly using one specific mode of operation throughout 1632 days of a 5-year interval (1999)(2000)(2001)(2002)(2003). The velocity magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The control times for the SEA were the times of CG lightning strokes measured by the World Wide Lightning Location Network (WWLLN) (Dowden et al, 2008) from August 2003 to August 2004; the first year WWLLN was fully operational. Parkinson et al (2001) and Kumar et al (2008) previously analysed the geomagnetic effects on the Bundoora database. Later, Kumar et al (2009) investigated the response of the F-region vertical drift due to CG lightning strokes located within 600 km of Bundoora.…”
Section: Introductionmentioning
confidence: 99%
“…The control times for the SEA were the times of CG lightning strokes measured by the World Wide Lightning Location Network (WWLLN) (Dowden et al, 2008) from August 2003 to August 2004; the first year WWLLN was fully operational. Parkinson et al (2001) and Kumar et al (2008) previously analysed the geomagnetic effects on the Bundoora database. Later, Kumar et al (2009) investigated the response of the F-region vertical drift due to CG lightning strokes located within 600 km of Bundoora.…”
Section: Introductionmentioning
confidence: 99%
“…We addressed this problem by creating a statistical model using the 5.5-year F-region database, with the results separated into two representative seasons, the spring-summer months (September-February) and autumn-winter months (MarchAugust). Also, it was found the drift magnitudes were generally larger than usual in the year 2003 (Kumar et al, 2008) due to the high-speed solar wind streams known to re-occur during the declining phase of solar activity (e.g. Cliver et al, 1996).…”
Section: F-region Datamentioning
confidence: 96%
“…The use of a long integration time (40.96-s) and thus high Doppler resolution meant that our estimates of vertical velocity V z were very accurate (Parkinson et al, 2001). Kumar et al (2008) analysed the entire DPS-4 F-region database and found that the velocities exhibited well-defined diurnal and seasonal variations with strong sensitivity to AE. The results were consistent with earlier studies using incoherent scatter radar (e.g.…”
Section: F-region Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The F region electric field drifts are believed to be caused by differences in the ionisation (Kelley et al, 1979;Kumar et al, 2008). The study of low latitude ionospheric electric fields and currents by Fejer (2003) using incoherent scatter radar measurements from Arecibo (181N, 671W, dip latitude 301N) and Jicamarca (11.91S, 76.81W, dip latitude 11N) showed that F2 region parameters (e.g.…”
Section: April 2001 Sf Eventmentioning
confidence: 99%